Dragoun, Michal et al. Knižní kultura českého středověku [Czech Book Culture in the Middle Ages]. Vydání první. Dolní Břežany: Scriptorium, 2020. 399 pp. ISBN 978-80-7649-012-3. - Brozovska Onderkova, Jana (Folia Toruniensia, 2024)
The monograph Knižní kultura českého středověku [Czech Book Culture in the Middle Ages] presents in four chapters the history of the manuscript and partially printed books and book culture, especially the area of book painting and book binding in the Czech lands in the Middle Ages until about the end of the 15th century. There is also an additional topic connected with book history, the period of incunabula. The authors of the individual chapters are Michal Dragoun, Jindřich Marek (Institute of Information Studies and Librarianship, Faculty of Arts, Charles University), Kamil Boldan (National Library of the Czech Republic), Milada Studničková (Institute of Art History, Czech Academy of Sciences). It summarizes new knowledge in areas previously summarized in the publications published in the early 1990s, Česká kniha v proměnách staletí [Czech Book through the centuries], compiled by a collective of authors under the leadership of Mirjam Bohatcová, and Josef Krása’s study České iluminované rukopisy 13.–16. století [Czech Illuminated Manuscripts 13th to 16th centuries]. The reviewed book is based on many years of research done by the members of the author’s team and also on partial studies by personalities of Czech and Moravian codicology and library science (e.g., Jiří Hlaváček, Petr Voit, Ladislav Dokoupil, and others).